2015
DOI: 10.1088/0957-4484/26/40/405704
|View full text |Cite
|
Sign up to set email alerts
|

Tunability of exchange bias in Ni@NiO core-shell nanoparticles obtained by sequential layer deposition

Abstract: Films of magnetic Ni@NiO core-shell nanoparticles (NPs, core diameter d ≅ 12 nm, nominal shell thickness variable between 0 and 6.5 nm) obtained with sequential layer deposition were investigated, to gain insight into the relationships between shell thickness/morphology, core-shell interface, and magnetic properties. Different values of NiO shell thickness t(s) could be obtained while keeping the Ni core size fixed, at variance with conventional oxidation procedures where the oxide shell is grown at the expens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…For example, oxidizing pure Ni nanoparticles (Koga and Hirasawa 2013), or using chemical reactive processes to grow Ni (Gang Wu et al 2010) or NiO (El-Kemary et al 2013). A common issue is the difficulty in precisely controlling the level of oxidation of the nanoparticles (i.e., the relative composition of Ni and NiO) or to have a structure other than a metallic core and oxide shell in a single-step approach (Spadaro et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxidizing pure Ni nanoparticles (Koga and Hirasawa 2013), or using chemical reactive processes to grow Ni (Gang Wu et al 2010) or NiO (El-Kemary et al 2013). A common issue is the difficulty in precisely controlling the level of oxidation of the nanoparticles (i.e., the relative composition of Ni and NiO) or to have a structure other than a metallic core and oxide shell in a single-step approach (Spadaro et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the EB can pin the spins in the FM material and stabilize their alignment along a magnetically pre-definite direction, increasing the magnetization stability [2,6]. This effect was exploited in core-shell NPs with a FM metal core and an AFM oxide shell, like Co@CoO and Ni@NiO systems [2,4,7,8]. In the case of Co@CoO NP films, it was found that T B , coercivity, and the EB field increase with the NP areal density, due to a modification of the magnetic properties caused by the neighboring oxide shells coming into contact, and providing a more efficient exchange interaction with the FM cores [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in the so-called sequential layer deposition mode, the NP can be embedded within two layers evaporated by MBE. The shells can be made of either metals or oxides, if the codeposition is performed in oxygen atmosphere [7,[20][21][22]. By this method it was possible to perform a systematic and accurate investigation of the morphology, structure and magnetic properties of Ni@NiO core-shell NPs by a number of different techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In particular particle systems consisting of 3d transition metals and their oxides have shown the exchange bias (EB) effect and related phenomena with interesting applications, which can improve the performance of permanent magnetic materials, i.e. an enhancement of the coercivitytypically a shi of hysteresis loop, 9,10 and combating the superparamagnetic limit in magnetic recording media. 11,12 The Co/ CoO core-shell structure is one of the most thoroughly studied systems whose EB behavior was observed in the coreshell structure at the ferromagnetic/antiferromagnetic (FM/ AFM) interface for the rst time.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are critical especially in nanosized crystals and are strongly affected by the synthetic route. Remarkable progress has been made in recent years regarding the synthesis of the Ni/NiO binary manoparticles., 10,12,[17][18][19][20] Highly crystalline and monodisperse Ni/NiO nanoparticles have been prepared by the physical techniques including laserinduced reductive sintering, 3 sequential layer deposition, 10 CVD method, 21 nanosecond laser irradiation, 22 cluster-beam deposition, 23 and pulsed laser deposition. 24 However, universal agreement of the origin of the EB effect and other related anomalous magnetic properties is still under debate.…”
Section: Introductionmentioning
confidence: 99%